Pengembangan Media Promosi untuk Meningkatkan Strategi Pemasaran Online UMKM di Kota Payakumbuh - Rasyid, Hanifa Corrina; Annas, Firdaus; Wandira, Raju (Yayasan Lembaga Studi Makwa, 2023)
Several MSMEs in Payakumbuh should be further disseminated so that they can be known in various countries, not only in the city of Payakumbuh. Promotions from several MSMEs have used social media, but still around the city of Payakumbuh, not yet known by the community from various provinces and even other countries. In fact, with this promotional method, it should have been known quite widely in Indonesia. The study aims to develop OpenCartbased promotional media to improve the online marketing strategy of MSMEs in the city of Payakumbuh. Various MSMEs in the city of Payakumbuh have great potential to grow and attract customers from a wider market, both nationally and internationally. However, their promotions are still limited to the use of social media with limited reach. The type of research conducted using the Research and Development (R&D) method, which is used to produce and test a product. This research model follows the 4D approach (Define, Design, Develop, Disseminate). The results of this study are in the form of a websitebased promotional media using the OpenCart application. The contribution of this research can improve the online marketing strategy of MSMEs in the city of Payakumbuh so that they can be known more widely. The initial stage involved interviews with MSME actors to understand their challenges. At the design stage, it was made with typical Minangkabau visual elements to reflect local cultural identity. Furthermore, development was carried out using OpenCart with complete online transaction features and search engine optimization. The results showed that the OpenCart-based platform significantly increased marketing reach and customer interaction. The importance of integrating digital technology and local culture in modern marketing.